Arsenic Linkage in the Irrigation Water-Soil-Rice Plant Systems (Biological Sciences - PJSIR, 2007)
. This investigation reports the levels of arsenic (As) i n i rrigation waters, soi ls and Boro (dry season) rice grai n from I 00 shallow tube well (STW) areas over the sadar u pazila of Chapai Nawabganj. The As concentrations for all samples (soil , water and rice grain) varied widely between locations. The shallow tube well (STW) water As concentration ranged from 0.015-0.352 µglml with a mean of 0.075 µglml , the concentration bei ng lower i n shallow wel l depth , reachi ng to a max i m um about at 25 m depth and then decreased with i ncreasi ng depths. The levels of total As i n soi ls over th e location s ranged from 5.8-17.7 µgig with a mean of 1 1.2 µgig. Total As content i n soi ls was positivel y correlated with i rrigation water-As i ndicati ng a possibil ity of As bui ld up i n soi l with ti me. The rice grain As concentration was i n the range of0.24-1.30 µlg g havi n g a mean of 0.76 µgig. 22% of the grai n samples had As leve l